(untitled) (Andamios, Revista de Investigación Social, 2004)
Without having tried to sketch an exhaustive review of the Witt- gensteinian outlook, I try to demonstrate that, precisely because of its remarkable therapeutic character, it has a profound practical relevance as well. I hold that the Wittgensteinian conception of philosophical thinking can provide a new path to think about the realm of the public. More so, its invitation to watch carefully contains a strong liberating impulse.